2010
DOI: 10.1093/nar/gkq575
|View full text |Cite
|
Sign up to set email alerts
|

A myriad of miRNA variants in control and Huntington’s disease brain regions detected by massively parallel sequencing

Abstract: Huntington disease (HD) is a neurodegenerative disorder that predominantly affects neurons of the forebrain. We have applied the Illumina massively parallel sequencing to deeply analyze the small RNA populations of two different forebrain areas, the frontal cortex (FC) and the striatum (ST) of healthy individuals and individuals with HD. More than 80% of the small-RNAs were annotated as microRNAs (miRNAs) in all samples. Deep sequencing revealed length and sequence heterogeneity (IsomiRs) for the vast majority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
251
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 285 publications
(273 citation statements)
references
References 64 publications
18
251
2
2
Order By: Relevance
“…We don't know whether these miRNAs are altered in patients of HD, except for miR-146a, which is increased in HD patients. 12 We have shown earlier that expression of this miRNA is decreased in in STHdh Q111 /Hdh Q111 cells. These miRNAs together may alter many genes other than HTT and thus further studies are required using either human HD samples or animal models.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 80%
See 3 more Smart Citations
“…We don't know whether these miRNAs are altered in patients of HD, except for miR-146a, which is increased in HD patients. 12 We have shown earlier that expression of this miRNA is decreased in in STHdh Q111 /Hdh Q111 cells. These miRNAs together may alter many genes other than HTT and thus further studies are required using either human HD samples or animal models.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 80%
“…11 In high throughput RNA sequencing assay, it has been shown that 51 miRNAs are increased, while 35 miRNAs are decreased in the brains of HD patients. 12 A comprehensive list of miRNAs, altered in the postmortem brains of HD patients and HD models have been tabulated (Sup. Table 1).…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have demonstrated the importance of miRNAs in the pathophysiology of several neuropsychiatric disorders and mental retardation syndromes (Conrad et al 2010;Sulzer 2011), including schizophrenia (Burmistrova et al 2007;Beveridge et al 2010;Moreau et al 2011;Santarelli et al 2011), bipolar disorder, Fragile X mental retardation (Edbauer et al 2010;Krol et al 2010;Wulff et al 2011), Rett syndrome (Wu et al 2010), Alzheimer's disease, Parkinson's disease (Junn et al 2009), and Huntington's disease (Martí et al 2010). A number of the cocaine-responsive miRNAs identified in this study are important in controlling dendritic morphology; these miRNAs, and many others, may contribute to long-lasting forms of drugmediated synaptic plasticity through control of regulatory Lugli et al 2008 (adult mouse cortex and hippocampus; measured by microarray) with RNA-Seq data (adult mouse striatum) from these experiments (Lugli et al 2008).…”
Section: Discussionmentioning
confidence: 99%